SYMBOLS OF WOMEN'S EXISTENCE IN SA,O NGGUA ORNAMENTS IN THE WOLOTOPO TRADITIONAL VILLAGE, EAST WOLOTOPO VILLAGE NDONA DISTRICT, ENDE DISTRICT - Kusi, Josef; Husen, Safina (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The problem in this research is what is the meaning of the symbol of women's existence in traditional house ornaments in the Wolotopo traditional village, East Wolotpo Village, Ndona District, Ende Regency. The aim of this research is to find out the meaning of the symbol of women's existence in traditional houses in the Wolotopo traditional community, East Wolotopo Village, Ndona District Ende Regency. The research method used in this research is a qualitative research method, with data collection techniques of observation, interviews and documentation. Meanwhile, the data analysis techniques in this research include data reduction, data presentation and conclusions. The results of the research show that the Wolotopo indigenous people believe that breast ornaments in traditional houses indicate the importance of women's role as a symbol of life and fertility for all humans, which is an ancestral heritage. This symbolizes unity and is a symbol of communication between humans and the highest being. In the life of the Wolotopo traditional community, women have an important role and big responsibilities, which have been inherited by their ancestors and are trusted by the local cultural community, such as women's involvement in traditional household affairs, in various traditional rituals such as working on traditional houses, mosalaki burial rituals and someone's coronation. becoming a traditional figure (wakelaki ritual), opening new land and making statues of gods (Ana deo).